The science of grapevines : anatomy and physiology - Keller, Markus (Academic Press, 2010)
Explores the physiology of the grapevine as it occurs around the world. This book addresses not only the specific issues and concerns of grapevines from regions around the world, but includes topics such as global climate change, water relations, temperature effect and more.